Legal Protection for Victims of Traffic Accidents Based on Justice (Cirebon Police Case Study) - Sijabat, Niko Andri; Laksana, Andri Winjaya (Jurnal Hukum Khaira Ummah, 2025)
Traffic accidents not only cause material losses, but also psychological and social impacts on victims. Therefore, a legal protection mechanism is needed that is not only repressive, but also restorative, in order to guarantee the rights of victims fairly and proportionally. The research method used is empirical juridical, with a qualitative approach. Data were obtained through interviews with law enforcement officers at the Cirebon Police, accident victims, and a review of relevant legal documents. The results of the study indicate that although legal protection has been regulated in laws and regulations such as Law No. 22 of 2009 concerning Traffic and Road Transportation and the Criminal Procedure Code, its implementation still faces obstacles, including minimal legal assistance for victims, lack of public understanding of victims' legal rights, and limitations in the application of restorative justice. This study recommends the need to increase the role of the Cirebon Police in socializing victims' rights, strengthening coordination with legal aid institutions, and implementing a more optimal restorative justice approach so that victims' rights can be fulfilled comprehensively.